On identifying name equivalences in digital libraries. Name equivalence, Surname matching, Author identification, Databases - Dror G. Feitelson (Information Research: An International Electronic Journal, 2004)
The services provided by digital libraries can be much improved by correctly identifying variants of the same name. For example, this will allow for better retrieval of all the works by a certain author. We focus on variants caused by abbreviations of first names, and show that significant achievements are possible by simple lexical analysis and comparison of names. This is done in two steps: first a pairwise matching of names is performed, and then these are used to find cliques of equivalent names. However, these steps can each be performed in a variety of ways. We therefore conduct an experimental analysis using two real datasets to find which approaches actually work well in practice. Interestingly, this depends on the size of the repository, as larger repositories may have many more similar names.